Ásgrímur Jónsson. The early watercolours 1904-1914 - Mundell, Derek Karl, 1951- (2011)
This thesis investigates the early watercolours of Ásgrímur Jónsson (1876–1958) painted between 1904 and 1914. The artist returned from Denmark in 1903 without any formal training in the use of watercolours. He proceeded to teach himself to use this difficult medium to interpret the Icelandic landscape during the new wave of Romanticism which was sweeping through Icelandic culture at the turn of the century. He commented in his memoirs which were published in 1956, that he had learnt most about watercolour by studying works by the British master J.M.W Turner (1775–1851). Studies were made for this thesis to determine which of Turner’s works Jónsson is likely to have seen during these formative years. Only one exhibition of British art was held in Copenhagen while Jónsson lived in Denmark. Five oil paintings by Turner were exhibited at that time. Other evidence indicates that Jónsson purchased illustrated art books and used the coloured prints therein to improve his watercolour technique at this time. A brief summary is made of technical terms connected with watercolour painting including an overview of materials. This enabled an empirical comparison to be made of selected examples of Jónsson’s watercolours dated 1904 to 1914, with works by Turner and other painters of the British school. Certain links were established but it was also noticeable that Jónsson was in fact more of a ‘purist’ than the British painters because he did not use gouache (bodycolour) in any of his works from this period. Jónsson reached a certain pinnacle in his large panoramic watercolours from Austur-Skaftafellssýsla which he painted in the years 1911 to 1913. He subsequently ceased painting landscapes in watercolour in 1914, and commented in his memoirs that he felt at that time that his art was becoming a routine skill and this was detrimental to his artistic development. It is reasoned in the thesis that in 1913–14 he was repeating popular landscape motives for sale and although this helped him financially, it meant that he was unable ...